The quest for improving general and in hospital health care during COVID-19 pandemic - Ridolo, Erminia; Incorvaia, Cristoforo; Gritti, Bruna; Pucciarini, Francesco (Acta Biomedica Atenei Parmensis, 2021)
Since January 2020 the COVID-19 pandemic has emerged as a serious public health problem (1), which -according to the 13 August 2021 WHO update- is burdened by 205.338.151 cases and 4.333.094 deaths (2). [...]